Closure strategies to mitigate future respiratory pandemics - Patrick Doohan; Rob Johnson; Alessandra Løchen; Christian Morgenstern; David Haw; Alice Sabino; Edith Patouillard; Giovanni Forchini; Katharina D. Hauck (Nature Health, 2026)
Abstract There is scant evidence on the broader societal losses of different pandemics, although this is crucial for evaluating mitigation strategies and quantifying the benefits of pandemic preparedness investments. Here we project the socioeconomic loss of respiratory pandemics, the sum of health, economic and educational losses, under four reactive business- and school-closure strategies, six hypothetical diseases and three country-income groups using epidemiological-economic modelling. The socioeconomic loss varies considerably between pandemics, with means ranging (as percentage of annual gross domestic product) from 2.9% to 439%, 2.3% to 360% and 1.9% to 290% in low- to lower-middle-, upper-middle- and high-income countries, respectively. Stringent closure strategies are more likely to minimize losses for severe diseases, high-income countries and higher life-year valuations. Strategies with reactive school- and business-closures usually outperform those with long-term school-closures, but the latter may be preferable under fiscal or political constraints. These findings provide decision-makers with initial evidence to better prepare for and respond to future pandemics.